PEMBUATAN MEDIA PEMBELAJARAN AUDIO-VISUAL UNTUK MATERI SISTEM PEMINDAH TENAGA OTOMOTIF - Suyitno Suyitno (Pendidikan Teknik Otomotif, 2015)
This reseach has aim to: 1)know the process of interactive media development for technicalmeasurment, 2)know the efectiveness of interactive media development for technicalmeasurment.This study is research and development. It is located on Faculty of Teacher Training and EducationSciences, majoring on Vocational Education Muhammadiyah University of Purworejo. This objectof the study is interactive media in learning technical measurment. I use some questionaires andtests for collecting the data. Then these are analized by quantitative method.The results are: 1)the process of making interactive includeson three steps, they are: a)The needsanalysis, b)product development, including index design, navigation and contents, andc)individual, small group test and last product implementation. 2)this product can be used as amedia for comprehending the technical measurment. The point of this study is interactive media ismore effective than conventional media in comprehending the technical measurement. we cananalyze them by the average difference between two classes; conventional class reaches 6,50 andexperiment class reaches 7, 80.Keywords: Media, Teaching and learning, power train system